Strategi Peningkatan Minat Belajar Materi Sakramen Tobat Kelas VIII Melalui Metode Problem Based Learning - Harefa, Ideal; Lede, Yohanes Umbu (CT. Rajawali media Utama, 2024)
Interest is a feeling of preference, a sense of attraction, attention and motivation of a person or individual in a particular activity. This Classroom Action Research (CAR) aims to improve the learning interest of class VIII students of SMP Negeri 2 on the material of the Sacrament of Penance through the application of the Problem-Based Learning (PBL) learning model. This research is motivated by the low interest of students in learning the material, which has an impact on less than optimal understanding of the concept. This research was conducted in two cycles, with each cycle including the planning, action, observation, and reflection stages. In each cycle, students are faced with authentic problems related to the material of the Sacrament of Penance. They then work in groups to find solutions to these problems through structured learning activities. The results of the study in cycle I showed that student learning outcomes were still not optimal with an average presentation of grades obtained on all indicators, namely 70.25, including in the developing category according to expectations. This is due to the lack of student understanding of the learning methods applied. While in cycle II there was a significant increase in student learning outcomes with an average presentation of grades obtained for all indicators, namely 88.50, including in the proficient category. In addition, students also showed better abilities in analyzing problems, finding information, and presenting group work results. Thus, it can be concluded that the application of the PBL model can increase students' interest in learning.